Antifungal, antibiofilm, and antiproliferative activities of Guapira graciliflora Mart - Carolina Medeiros de Almeida; Rennaly de Freitas Lima; Tereza Karla Vieira Lopes da Costa; Ilza Maria de Oliveira Sousa; Elaine Cristina Cabral; Rosanna Tarkany Basting; Adriana Della Torre; Yuri Wanderley Cavalcanti; Pedro Luiz Rosalen; Marta Cristina Teixeira Duarte; Ana Lúcia Tasca Gois Ruiz; Mary Ann Foglio; et al. (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract: The aim of this study was to evaluate in vitro the antifungal, antibiofilm and antiproliferative activities of the extract from the leaves of Guapira graciliflora Mart. The phytochemical characterization of the extract was performed using electrospray ionization mass spectrometry (ESI-MS). The antimicrobial activity of the extract and its fractions was evaluated using the broth microdilution method against species of Candida. The inhibition of C. albicans biofilm was evaluated based on the number of colony-forming units (CFU) and metabolic activity (MTT). The antiproliferative activity of the extract and its fraction was evaluated in the presence of human tumor and non-tumor cells, and the cytotoxicity of the extract was determined on the RAW 264.7 macrophage line - both using the sulforhodamine B method. The phytochemical characterization indicated the presence of the flavonoids rutin and kaempferol. The extract and the methanol fraction exhibited moderate antifungal activity against C. albicans, C. krusei, and C. glabrata, and strong activity against C. dubliniensis. In the biofilms at 24 and 48 hours, the concentration of 12500 µg/mL of the extract was the most effective at reducing the number of CFU s/mL (44.4% and 42.9%, respectively) and the metabolic activity of C. albicans cells (34.6% and 52%, respectively). The extract and its fractions had no antiproliferative effect on the tumor lines tested, with mean activity (log GI50) equal to or greater than 1.71 µg/mL. Macrophage cell viability remained higher than 80% for concentrations of the extract of up to 62.5 µg/mL. G. graciliflora has flavonoids in its chemical composition and demonstrates potential antifungal and antibiofilm activity, with no evidence of a significant change in the viability of human tumor and non-tumor cell lines.